Pemilihan Karyawan Terbaik Berdasarkan Kinerja Karyawan dengan Menggunakan Metode Analytic Network Process (ANP) - Ibnu Rusydi; Suhardi Suhardi; Alviona Marsya (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Employees are workers who provide a service, usually in the form of energy or thoughts and get wages based on an agreement that has been mutually agreed upon. The purpose of this study is the selection of the best employees for promotion or salary increases which were previously subjectivity to objectivity. For this reason, it is necessary to have a decision support system for evaluating employee performance for promotion or salary increases using the Analytic Network Process (ANP) method. This method was chosen because it is able to complete employee performance appraisals based on the criteria that have been determined at the POM Stabat PT. Langkat Nusantara Kepong (LNK), namely, performance (job performance and results), technical competence and understanding of tasks, management and responsibilities, initiative and creativity in the context of work, flexibility and cooperation (within divisions or between divisions), discipline, commitment and motivation, carrying out the values of â€œKuala Lumpur Kepongâ€ (integrity, loyalty, humility) and late arrival to work, which will later be used as a reference in giving salary increases or promotions for the position itself. This system was developed with the Python programming language. The results of this study in the form of the application of the ANP method into the system with a manual calculation process concluded to have the same results in each process, so that the system that was built was deemed successful in determining who the best employees were entitled to a salary increase or promotion.